Telemedicine in Chile: use, development and controversies in a southern public health network of country - Villarroel, Sebastián; Medina, Sebastián (Revista Chilena de Salud Pública, 2022)
Introduction: Telemedicine emerges as a continuity alternative for health services in the pan¬demic context. Objectives: Our work analyzed the conditions for the use and development of telemedicine (remote video consultations) in a territorial context of high geographic dispersion and rurality, and an organizational context of public institutions working in networks chronically affected by the neoliberal reforms. Materials and Methods: We use a qualitative hermeneutical design based on semi-structured interviews with health teams and managers of a public healthcare network in southern Chile. Results: The results show benefits such as the proximity of the specialist with the territory, the learning between professionals and the continuity of care. Motivations, interests and resistance of health teams emerge as the main determinants of the use and development of telemedicine, with significant workload asymmetries in the clinical and resource management processes between levels of care. Discussions: The pandemic would have facilitated the increase of telemedicine, while its be¬nefits and effectiveness would depend on the value that teams place on it to support health care and its translation into collective learning for the institution, rather than compliance with regulatory frameworks. In this new scenario, it becomes a priority to explore the perceptions of users regarding the expansion of telemedicine.